Modelling of microalgal growth and lipid production in Dunaliella tertiolecta using nitrogen-phosphorus-potassium fertilizer medium in sintered disk chromatographic glass bubble column. (October 2016) - Kumar, Anup; Guria, Chandan; Chitres, G.; Chakraborty, Arunangshu; Pathak, A.K.
Highlights: Dunaliella tertiolecta cultivation using NPK-10:26:26 fertilizer. Modelling for biomass and lipid productivity under nutrient and environmental stress. Determination of biokinetic model parameters for algal growth. Model validation under varying NPK-10:26:26, NaCl, NaHCO3, light and temperature. Parametric sensitivity of biokinetic parameters for algal cultivation. Abstract: A comprehensive mathematical model involving NPK-10:26:26 fertilizer, NaCl, NaHCO3, light and temperature operating variables for Dunaliella tertiolecta cultivation is formulated to predict microalgae-biomass and lipid productivity. Proposed model includes Monod/Andrews kinetics for the absorption of essential nutrients into algae-biomass and Droop model involving internal nutrient cell quota for microalgae growth, assuming algae-biomass is composed of sugar, functional-pool and neutral-lipid. Biokinetic model parameters are determined by minimizing the residual-sum-of-square-errors between experimental and computed microalgae-biomass and lipid productivity using genetic algorithm. Developed model is validated with the experiments of Dunaliella tertiolecta cultivation using air-agitated sintered-disk chromatographic glass-bubble column and the effects of operating variables on microalgae-biomass and lipid productivity is investigated. Finally, parametric sensitivity analysis is carried out to know the sensitivity of model parameters on the obtained results in the input parameter space. Proposed model may be helpful in scale-up studies and implementation of model-based control strategy in large-scale algal cultivation.